Исследования геометрически нелинейных колебаний многослойных пластин сложной формы со слоями различной толщины - Курпа, Лидия Васильевна; Тимченко, Галина Николаевна (Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, 2014)
The problem of nonlinear free vibrations of composite laminated plates with layers of different thickness and complex planform is studied. The mathematical statement of the problem is carried out using the Timoshenko type theory. To solve the problem the R-function theory, variational methods and the Bubnov-Galyorkin method have been applied. The comparison of the obtained results with available ones confirms effectiveness and reliability of the offered method.
Ivestigation of geometrically nonlinear vibration of the laminated plates with complex form and layers of the different thickness
Keywords: метод численно-аналитический; теория R-функций; метод Ритца; метод Бубнова-Галеркина